DESKRIPSI PENERAPAN PEMBELAJARAN KELAS RANGKAP DI KELAS IV DAN KELAS V SEKOLAH DASAR NEGERI 34 SUNGAI RAYA - Muhammad Arrizallu Sholihin; Kartono Kartono; Dian Miranda; Siti Halidjah; Asmayani Salimi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe classroom management and learning implementation in the application of multiple-grade teaching in grades IV and V of Sungai Raya Public Elementary School 34. The study uses a descriptive qualitative approach. Data were collected through observation, in-depth interviews (with teachers, principals, and students), and documentation studies. The data analysis technique followed the interactive model of Miles and Huberman. The results of the study show: (1) Classroom management includes efforts to create an optimal situation (motivation, ice breaking), overcome deviant behavior (class agreements, appreciation, reprimands), and classroom layout arrangements that divide the space and blackboard for two classes. (2) The implementation of learning follows the PKR 221 model, with planning using separate teaching modules; implementation is divided into introductory and closing activities that are carried out together, as well as core activities that are carried out separately/alternately; evaluation includes student and teacher reflection and peer assessment. Double-shift learning can be implemented effectively despite limited resources, through structured classroom management and adaptive learning planning. The integration of teaching modules and expansion of research in other subjects are recommendations for future development.